2015
DOI: 10.1097/hjh.0000000000000651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of arterial stiffness with cardio-ankle vascular index

Abstract: Arterial stiffness is often assessed in clinical medicine, because it is not only an important factor in the pathophysiology of blood circulation but also a marker for the diagnosis and the prognosis of cardiovascular diseases. Many parameters have so far been proposed to quantitatively represent arterial stiffness and distensibility, such as pressure-strain elastic modulus (Ep), stiffness parameter (β), pulse wave velocity (PWV), and vascular compliance (Cv). Among these, PWV has been most frequently applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 76 publications
2
118
0
3
Order By: Relevance
“…Major conventional index is known as cfPWV (carotid-femoral PWV), hfPWV (heart-femoral PWV), baPWV (brachial-ankle PWV) and haPWV (heart-ankle PWV) [8]. However, those methods require to attach cuffs or electrodes to the body.…”
Section: Proposed Measurement Methodsmentioning
confidence: 99%
“…Major conventional index is known as cfPWV (carotid-femoral PWV), hfPWV (heart-femoral PWV), baPWV (brachial-ankle PWV) and haPWV (heart-ankle PWV) [8]. However, those methods require to attach cuffs or electrodes to the body.…”
Section: Proposed Measurement Methodsmentioning
confidence: 99%
“…where P s and P d are systolic and diastolic blood pressures, and ρ is the blood mass density [17,18]. Pressures, PWV, and ρ should be entered into equation 1 in units of Pa, m/s, and kg/m 3 , respectively to ensure dimensional correctness.…”
Section: Option 1: Converting Pwv Into Blood Pressure-independent Meamentioning
confidence: 99%
“…Segers [35] acknowledges this effect in his editorial comment, in which he illustrates the blood pressure dependence of β by plotting In( P / P ref ) versus d / d ref . The slope of this plot, which is equal to β [18], changes when changing P ref and d ref , as is the case when diastolic blood pressure is used in calculating β.…”
Section: Option 1: Converting Pwv Into Blood Pressure-independent Meamentioning
confidence: 99%
“…Compared with PWV, CAVI does not depend on the immediate effect of blood pressure. CAVI comes from the stiffness coefficient β and can be calculated by the electrocardiogram, phonocardiogram, and brachial ankle artery pulse waveform and pulse waveform records and is mainly related to aortic stiffness and compliance [29]. A series of studies have found that CAVI as a new marker of vascular health was closely related to arterial injury in patients with hypertension, diabetes, metabolic syndrome, and blood lipid disorder and became a useful tool for health screening because of the blood pressure dependence [3035].…”
Section: Evaluation Of Arterial Stiffnessmentioning
confidence: 99%